Indigenous knowledge in Borneo: a bibliometric review - Wan Abdul Rahman, Wan Bujang; Norlina, Kadri (2021)
The paper is to presents a bibliometric review of the research publication output of indigenous knowledge in Borneo. This study adopted a bibliometric analysis based on the data obtained from the Scopus research database. The main keyword used is “Borneo”, to highlight research relevant that reflected through its publications and their research productivity. This study attempts to focus analyses the results using standard bibliometric indicators such as publication year, document type, source type, source title, languages, subject area, keywords analysis, geographical distribution, authorship, active institutions, and citation analysis on the subject of “Borneo” throughout 5 years (2017-2021) impact study. From the major findings, Universiti Malaysia Sabah and Universiti Malaysia Sarawak from Malaysia are the institutions and country that produced the most publications output on this study. The study also shows the results on the most subjects are in agricultural and biological sciences, arts, and humanities, biochemistry, genetics, and molecular biology. Besides that, this study aims to facilitate the search for information, bibliography materials and knowledge topics, especially on Borneo.